Assessing the Contribution of Clastic Sedimentary Rocks to Geosite Potential and Geoscience Education: An Example of Coarse-grained Turbidite Sequences, Baskil (Elazig, Turkiye) - Alkac, Onur; Koroglu, Fatih; Mulayim, Oguz (Springer Heidelberg, 2024)
Geosites today are natural sites consisting of rocks, minerals, fossils, and landforms that represent the major geological processes of our 4.54 billion-year-old Earth and are remarkable in terms of their formation and appearance in nature. The potential geosite area to be investigated covers an area of 40 km(2), similar to 40 km southwest of the Baskil district of Elazig. Clastic sedimentary rocks with potential geosite belong to the Kirkgecit Formation and consist of coarse-grained turbiditic sand-stones. The geologically significant rocks found in the Lateral Accretion Package include the Bouma sequence, ripple marks, flute marks, long-axis imbrications, planar cross-bedded and ichnofossil sedimentary structures. These sedimentary structures are of crucial importance for understanding this ancient geoid and preserving its typical locations for future generations. In this study, the sedimentary structures in the siliciclastic, coarse-grained turbidite sediments filling the Elazig Basin were investigated. These sedimentary structures in clastic sedimentary rocks are becoming increasingly accessible for scientific research and are likely to play an important role in the development of potential geosites. It is recommended that these natural areas be protected and their contribution to geoscience education assessed.
Keywords: Coarse-grained Turbidite; Geoheritage; Geoscience Education; Sedimentary Clastic Rocks